Transformasi Penegakan Hukum di Era Kecerdasan Buatan: Analisis Normatif terhadap Kebutuhan Reformasi Regulasi Hukum Pidana dan Acara Pidana di Indonesia - Ayu, Rara; Karna, Wijaya; Wibowo, Beni (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The development of artificial intelligence (AI) has begun to influence the manner in which criminal law enforcement is conducted, including through practices such as predictive policing, police data analytics, and the integration of intelligent systems into judicial administration. International studies indicate that while AI offers efficiency gains, it simultaneously poses risks of algorithmic discrimination, data bias, privacy violations, and uncertainty regarding legal accountability in law enforcement contexts (González et al., 2021; Perry et al., 2013). In Indonesia, normative legal analyses demonstrate that AI is currently classified as an electronic system or electronic agent rather than a legal subject; consequently, criminal liability for the use of AI remains attributed to the individuals or legal entities operating such systems (Haris & Tantimin, 2022; Rahman, 2019). This study aims to analyze the need for regulatory reform in Indonesian substantive criminal law and criminal procedure in response to the utilization of AI in law enforcement, with particular emphasis on the principles of legality, due process of law, personal data protection, and human rights. The research employs a normative juridical method by examining relevant statutory frameworks (the Criminal Code, Criminal Procedure Code, Electronic Information and Transactions Law, and Personal Data Protection Law) as well as scholarly literature on AI, predictive policing, and criminal liability in Indonesia and other jurisdictions (Haris & Tantimin, 2022; Rahman, 2019; Saputra, 2025). The findings reveal significant normative gaps concerning standards for AI use across all stages of the criminal justice process, the absence of risk-based classification, and the lack of clarity regarding the allocation of responsibility among developers, providers, and users of AI systems. The study further indicates that reliance on predictive outputs as a basis for legal action may potentially conflict with the presumption of innocence and the principle of non-discrimination if not subject to strict regulation (Rahman, 2019; Saputra, 2025). Accordingly, this research recommends the establishment of a specific regulatory framework that classifies AI systems in the law enforcement sector as high-risk technologies, mandates human rights and data protection impact assessments, and ensures meaningful human control over all decisions affecting individual liberty (Saputra, 2025; Wibowo, 2023).